THE EDUCATIONAL SIGNIFICANCE OF HUMAN RIGHTS AND ISLAMIC VALUES - Ametov, Akhmet Qulametovich (SCIENCE and SOCIETY, 2026)
The article explores human rights and the importance of Islamic spiritual values in shaping and educating a modern, developed personality. It analyzes the guarantees of freedom of conscience and religion in the renewed Constitution of Uzbekista.
Keywords: human rights; freedoms; freedom of conscience; freedom of religion; constitution; value; religious value; universal human value; virtue